Inflammatory markers are beneficial in the early stages of cerebral venous thrombosis - Aysel Tekesin; Abdulkadir Tunç (Arquivos de Neuro-Psiquiatria)
ABSTRACT Cerebral vein thrombosis (CVT) is a rare but serious cause of acute stroke. Inflammation is a hypothetical etiological factor in CVT. Objective: The aim of this study was to evaluate inflammatory marker levels in CVT patients and compare these with healthy individuals. Methods: This prospective case-control study was conducted with 36 newly-diagnosed CVT patients age- and sex-matched with 40 healthy individuals. The laboratory investigations included a serum hemogram, full biochemistry profiles, high sensitivity C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-HDL cholesterol ratio (MHR) values were calculated and compared between the patients and healthy participants. Results: The mean age was 41.4 ± 11.8 years for patients, and 39.3 ± 12.5 for controls. Lymphocyte, total bilirubin, indirect bilirubin, and HDL levels were significantly lower in CVT patients (p < 0.05), while CRP, and ESR values were significantly higher. In the CVT patients the mean NLR and PLR values were significantly higher than in the control individuals. Smoking rates, alcohol consumption, white blood cell, neutrophil, platelet, and MHR values were similar in both groups (p > 0.05). Conclusions: We suggest that NLR, PLR, CRP, ESR, and bilirubin can be used in clinical practice for prediction of CVT in suspected patients as they are inexpensive parameters and widely available. However, further large-scale studies are required to confirm this relationship.